Input of Antenatal Care in Perinatal Mortality in the Tertiary Care Center, PUMHS Nawabshah - Arif, Iqra; Noor, Aisha; Khatoon, Nawab; Farhat; Azeem, Sana; Kainaat; Raishem (Indus Journal of Bioscience Research, 2025)
Background: Perinatal mortality remains a critical public health challenge in Pakistan, despite advances in maternal healthcare. High-quality antenatal care (ANC) can significantly reduce perinatal deaths through early detection and management of maternal complications. Objective: To evaluate the impact of antenatal care adequacy, timing, and quality on perinatal mortality among obstetric patients at a tertiary-care center in Sindh, Pakistan. Methodology: A descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Peoples University of Medical & Health Sciences for Women (PUMHS), Nawabshah, from May to November 2024. Data from 210 women delivering at ≥28 weeks gestation were analyzed. Maternal demographics, ANC characteristics, and perinatal outcomes were recorded. Data were analyzed using SPSS v26, applying descriptive statistics, Chi-square tests, and logistic regression. Results: The perinatal mortality rate (PMR) was 133.3 per 1000 births. Adequate ANC was associated with a lower mortality rate (8.8%) than inadequate ANC (15.5%) (p=0.265). Antepartum hemorrhage (AOR 2.95) and ANC inadequacy (AOR 2.03) were key predictors of perinatal death, while higher birth weight and gestational age were protective. Conclusion: Improving ANC adequacy and early registration, coupled with better screening for anemia and hemorrhage, could markedly reduce preventable perinatal deaths. Strengthening ANC quality and referral mechanisms is essential to achieve Pakistan’s maternal–child health targets.